Elite badminton is getting older: Ages of the Top 100 ranked badminton players from 1994 to 2020 - Abián, P.; Simón-Chico, L.; Bravo-Sánchez, A.; Abián-Vicén, J. (International Journal of Environmental Research and Public Health, 2021)
The purpose of this study was to determine the evolution of the age of badminton players in the top 100 of the World Ranking for men and women from 1994 to 2020. Data were collected from badminton players participating in the top 100 World Rankings (4800 entries: 1233 players; 595 men and 638 women) from 1994 to 2020. The mean age of the top 100 and the average highest ranking of the players were analysed for both genders. The mean age of the male players in the World Ranking increased from 23.7 ± 3.2 years in 1994 to 26.3 ± 4.4 years in 2020 (p < 0.001) and in female players, from 22.8 ± 3.8 years in 1994 to 24.7 ± 3.3 years in 2020 (p < 0.001). In addition, women recorded a younger age at entry into the top 100 and when reaching their best ranking. Additionally, there has been a clear increase in Asian players in the top 100 of the World Ranking in recent years, reaching over 60%. These data could be used to develop and organise training plans in this sport, optimising and maximising players` performance.